A novel method for sensitive detection of Escherichia coli O157:H7 based on an aptamer and hybridization chain reaction. Issue 29 (13th July 2020) - Liu, Yuexin; Chen, Ping; Yuan, Shuai; Sun, Bo; Sun, Rui; Meng, Xianghui
Abstract : A novel assay for the sensitive detection of E. coli O157:H7 using an aptamer-based HCR, which provided a universal platform for other bacterial detection. Abstract : This work developed a novel assay for the detection of Escherichia coli O157:H7 ( E. coli O157:H7), which is based on the specific recognition of an aptamer (H0) for E. coli O157:H7, the signal amplification of a hybridization chain reaction (HCR) and the adsorption and quenching effect of graphene oxide (GO). The feasibility of this work was verified through control experiments. The concentration of GO, the HCR time, the concentration of H0, and the concentration of H1/H2 were optimized. A series of E. coli O157:H7 dilutions were detected under the optimal conditions, and the detection range was 2.6 × 10 2 to 2.6 × 10 8 CFU mL −1 . The linear equation is y = 591.1 x − 943.9, R 2 = 0.995, and LOD is 5 × 10 1 CFU mL −1 . Milk samples were used for the spike recovery experiment, and the recovery rate was 92.6–103.6%. This method shortens the detection time greatly and provides a new strategy for food safety monitoring.